PERENCANAAN PARKIR STASIUN LRT DJKA DALAM RANGKA PENINGKATAN PELAYANAN LRT SUMATERA SELATAN - Muntaha, Moh. Khoirul; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
DJKA LRT Station or called DJKA Station is the final station of the South Sumatra LRT cross service and is located on Jalan Gubernur H. Bestari (National Road). Currently, DJKA station does not have parking facilities but uses sidewalks and part of the road for parking cars and motorbikes for LRT station officers and bicycles for cycling passengers, which is contrary to existing regulations. Therefore, this study aims to plan parking facilities at DJKA Station both in terms of parking rates, parking space requirements and parking design with interview and preference survey methods and analysis of parking demand calculations. The results of the analysis found that parking preferences of station staff respondents and LRT passengers agreed and would use parking facilities with a type of tariff, namely a flat rate per entry per day of Rp. 2,000 for motorbikes and Rp. 5,000 for cars. Overall parking space requirements are 202 SRP for motorcycles, 61 SRP for passenger cars gol. II, 1 SRP for vehicle car gol. III and 1 bicycle parking facility measuring 4m x 2m. By considering the availability of land and parking space requirements, the location of the parking area used is in the area west of DJKA Station and with an island parking pattern, a parking angle of 90 °, and the number of parking counters of 1 counter for both motorcycle vehicles (ρ value = 0.075 < 1) and car vehicles (ρ value = 0.003 < 1).Keywords: DJKA station parking, parking space, parking rates, parking design.